Prevalence of Clostridium difficile Isolated from Beef and Chicken Meat Products in Turkey - Ersöz, Şeyma Şeniz (Korean J Food Sci Anim Resour, 2018)
The concern about the possibility of food can be a vehicle for the transmission of Clostridium difficile to humans has been raised recently due to the similarities among the strains isolated from patients, foods and food animals. In this study, therefore, the prevalence of C. difficile was investigated in beef and chicken meat products collected from 57 different butcher shops, markets and fast food restaurants in Sakarya province of Turkey. Two out of 101 samples (1.98%) was positive for C. difficile indicating a very low prevalence. The pathogen was isolated from an uncooked meatball sample and a cooked meat döner sample, whereas not detected in chicken meat samples. The meatball isolate was resistant to vancomycin and tetracycline, while the cooked meat döner isolate was resistant to vancomycin and metronidazole. Both isolates were sensitive to moxifloxacin and clindamycin. Toxins A and B were not detected. This study reveals the presence of C. difficile in further processed beef products in Turkey.